Telaah Yuridis Aplikasi Zoom Dalam Mengumpulkan Data Pribadi Ditinjau Dari Peraturan Pemerintah No. 71 Tahun 2019 Tentang Penyelenggaraan Sistem Dan Transaksi Elektronik - Hendrawan Agusta (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Currently the world hit by the Covid-19 outbreak which makes physical meetings (offline) very limited. This challenge creates opportunities, one of which is for Zoom Cloud Meetings (Zoom) as one of the most widely used applications in Indonesia for online meetings. Zoom is the result of the development of information technology that creates a new style of communication, resulting in the Zoomdemic phenomenon. This application is a game changer in the midst of implementing Work From Home (WFH) in Indonesia. The use of Zoom requires a registration process which requires the collection of Personal Data from Users. Zoom is an Electronic System Operator that provides, manages and operates communication services including voice calls, video calls in the form of digital platforms. The author discusses the process of collecting and sharing Personal Data carried out by Zoom using legal rules regarding the implementation of electronic systems and transactions that apply in Indonesia.